Matéria orgânica e atributos físico-químicos de um Cambissolo submetido a diferentes usos agrícolas e manejo do solo no semiárido da Chapada do Apodi-RN - Marinho, Ana Cecília da Costa Sinclair (Universidade Federal Rural do Semi-Árido, 2014)
When handling the soil and the Savanna perceives its fragility in terms of decomposition of soil organic matter (MOS) and other attributes. The use of appropriate techniques to local agricultural peculiarities conditions taking into account the weather pattern, soil type and management of the Caatinga constitute an essential tool for maintenance of natural resources. With this study we sought a direction about the quantitative fractions of soil organic matter (MOS) and physico-chemical soil for different agricultural use and soil management, aiming to identify which of these were the most sensitive in distinguishing environments , and the Native Forest (AMN) as a reference, identifying which of these showed improvement and / or restrictions in the study sites. The research was conducted at Governador Dix-Sept Rosado, the Settlement Land of Hope Project located in the micro-region of Chapada Apodi-RN, in a Cambisol Eutrophic. The areas studied were: AMN - Native Forest area, AP - area Cajaraneiras orchard, APC - news area with conventional preparation of the soil in intercropping, ACOL - area of colluvium and AAG - Agro-ecological area. Soil fertility analyzes were performed, physical analysis such as resistance to penetration, particle size, bulk density and particle density, as well as total organic carbon analysis and labile and recalcitrant SOM. It was observed that the ground reaction as fertility study areas had neutral to alkaline reactions, without the presence of Al + 3 and Al + H, and no high salinity. The most organic material contribution in AP area (favored increased P, Ca + 2 and K + in the soil, and reduction in Mg + 2 levels and increased resistance to soil penetration, probably due to the trampling of animals. it is concluded that (AAG) retained condition similar to the AMN labile fractions C and recalcitrant organic matter (MOS), even reaching a IMC of 111 and major components shown that the chemical attributes (P, K +, and Ca + 2) and labile and recalcitrant fractions of soil organic matter (MOS) were indicators of separation of environments. However, the most sensitive were labile carbon and carbon management index
Organic matter and physical-chemical properties of a Inceptisol under different agricultural use and soil management in the semiarid region of Apodi-RN Chapada
Keywords: Caatinga; Agroecológico; Carbono orgânico; Resistência à penetração; Labilidade; Manejo do solo; Caatinga; Agro-ecological; Organic carbon; Penetration resistance; Lability; CIENCIAS AGRARIAS::AGRONOMIA::CIENCIA DO SOLO::MANEJO E CONSERVACAO DO SOLO